Ringkasan Disertasi : Konsep Aqabah Dalam Tasawwuf Al-Ghazali (Tela’ah atas kitab Minhaj al-‘Abidin) - Yedi Purwanto (Jurnal Sosioteknologi, 2006)
The classical work of Al Ghajali, Minhaj al-Abidin, describes the role of Ibadah or Islamic way of worshiping Allah (the almighty God)) in details. Ibadah is a compulsory duty of a moslem. To do the Ibadah rightly, a moslem is required to obey the suggested pointers (aqabah). He drew an analogy between aqabah and the idea of “climbing a path with many hindrances”. Aqabah consists of seven kinds. The first is aqabah al-ilm. This type of aqabah is applied in scientific endeavours. The second is aqabah al tawbah. This one is applied in purifying oneself from his sins. The third is aqabah al-awa‟iq,. This relates to things that prevent a moslem when worshiping Allah. The fourth is aqabah al-awaridh, which is related with anything in a life. The fifth is aqabah al-bawa‟ith, which relates to anything that encourages a Moslem to worship Allah. The sixth is aqabah al-qawadih, which concerns any bad nature that a moslem must avoid when worshiping Allah. And the last is aqabah al-hamd waal-shukr, which is about praising Allah. The terms of aqabah al-ilm, al-tawbah, al-bawa-ith, alhamd waal-sukr seem to have been interpreted wrongly by Al-Ghajali if a careful study is carried out on them. This is one of the weaknesses of Al-Ghajali‟s concept of aqabah in Minhaj al-Abidin. It is, therefore, suggested that the labels for the four aqabah terms above be as the following: aqabah of stupidity, sin, laziness, an arrogance respectively. It is predicted that someone who reads the later labels of aqabah may understand them better since the terms share similar meaning with the concepts. As for the other three aqabah terms, the meanings and their concepts are relevant that the changes of the terms made to them are not necessary.